A national survey on registered products, availability, prices, and affordability of 100 essential medicines in community pharmacies across Sri Lanka - Liyanage, Chiranthi Kongala; Gunawardane, Mekala; Kumaradasa, Pamodee Panchalee; Ranasinghe, Priyanga; Jayakody, Raveendra Laal; Galappatthy, Priyadarshani (BMC health services research, 2023)
Introduction Availability of essential medicines that meet the expected quality standards, in appropriate dosage forms at affordable prices is a fundamental prerequisite to fulfill healthcare needs of given a population. This study assessed available products, prices and affordability of essential medicines (EM) in community pharmacies in Sri Lanka with comparison of registration status from the National Medicines Regulatory Authority(NMRA). Methods A cross-sectional island-wide survey of 80 pharmacies was conducted according to World Health Organization and Health Action International Manual (WHO/HAI). Hundred medicines were selected from the global core list(n = 14), regional core list(n = 16) and the Sri Lanka Essential Medicine List (SL-EML) (n = 70) based on healthcare needs. Number of registered products in 2015 and 2021 were compared. Findings Average availability was 85.4%(± 12.31) and availability was lowest in the Northern province (69.38 ± 21.18%)(p = 0.008). Availability between the state owned, franchise and privately owned pharmacies was not significantly different (p > 0.05). 89.4% medicines were affordable except for amiodarone, hydroxychloroquine, sitagliptin, soluble insulin, isophane insulin, losartan, levodopa carbidopa combination, clonazepam and ceftriaxone. The median price ratio (MPR) of 33.7% of medicines was less than 1 and MPR of 37.1% originator brands (OB) was over 3. Median number of generic brands in the market was 8(range 2–44), 9% of medicines had 20 or more products in the market and 72.7% medicines had more products available than the number registered in 2015. The average number of registered products were similar in 2015 (8.27) and 2021(7.59) (p = 0.15). Conclusion The overall availability of EMs in Sri Lanka was high in all categories of community pharmacies. Medicines were largely affordable and reasonably priced in 2015, although OBs were generally more expensive. Majority of medicines had more products in the market than the number of registered products.